Can you be a follower even when you do not follow the leader? Yes, you can. (June 2021) - Almeida, Teresa; Ramalho, Nelson C; Esteves, Francisco
In the ongoing debate in the area of critical leadership studies, the nature of leader–follower relationships is a thorny issue. The nature of followership has been questioned, especially whether followers can display resistance behaviours while maintaining their follower position. Addressing this issue requires a dialectical approach in which followers and leaders alike are primary elements in leadership co-production. Followers who face destructive leaders are of special interest when leadership is studied as a co-creational process. This context favours the emergence of a full range of behavioural profiles in which passives and colluders will illustrate the destructive leadership co-production process, and those who resist demonstrate that followers may not follow the leader and still keep a followership purpose. A two-step data analysis procedure was conducted based on the behaviour descriptions of 123 followers having a destructive leader. A qualitative analysis (i.e. content analysis) showed a set of behaviours and their antecedents that suggest three main groups of followers: resisters, obedient and mixed behaviour. Treating these data quantitatively (i.e. latent class analysis), six followers' profiles emerged: active resistance, passive resistance, passive obedience, conflict avoidance, support and mixed. Our findings provide evidence that followers who resist may do it for the sake of the organisation. We discuss our findings in light of followership theory, whereby joining role-based and constructionist approaches allows us to argue that followers may still be followers even when they do not invariably follow their leader.